Efficacy of micronutrient seed priming on maize (zea mays) growth and yield in micronutrient soils in Limpopo Province - Rapetsoa, Mokgatla Collen (My University, 2019)
One of the major constraints to crop productivity in South Africa is crop nutrient deficiency especially micronutrients. Laboratory, glasshouse and field studies were carried out during the 2016/2017 growing season to assess the effects of micronutrient (Zn, B and Mo) seed priming on maize growth and yield in micronutrient deficient soils of the Limpopo province. The laboratory experiment was carried out in a completely randomized design (CRD) laid out in a 3 x 5 x 3 factorial treatment structure with three replications. The assessments of the micronutrients were made at 0%, 0.01%, 0.05%, 0.1%, and 0.5% concentrations. The seeds were primed in the solutions for 24 h, 12 h and 8 h. The glasshouse experiment was carried out in a completely randomized design (CRD) laid out in a 3 x 4 x 2 factorial treatment structure with three replications. In the field, a single factor experiment in a randomised complete block design (RCBD) with three replications and a control was used, with micronutrient concentrations as levels. The laboratory study investigated the effect of seed priming with Zn, Mo and B on germination (germination percentage (GP), germination rate (GR), the coefficient velocity of germination (CVG), days to germination (DG) and mean germination time (MGT)). The interaction between seed priming duration and concentration levels of seeds primed with B had significant effect (P < 0.05) on germination. The interaction between seed priming duration and concentration levels of seeds primed with Zn had significant effect (P < 0.05) on germination. The interaction between seed priming duration and Mo concentration levels on CVG, MGT and DE had no significant different (P > 0.05). Meanwhile, the effect on GP and GR had significant (P < 0.05) effects. Seed priming with the micronutrients and water resulted in improved GP, MGT and CVG for seeds primed with 0.01, 0.05 and 0.1% for 24 h in laboratory conditions. The glasshouse study was established to investigate the effect micronutrient seed priming on seedling establishment and growth. The effects of the interaction between Mo concentration levels and duration, Zn concentration levels and duration, B concentration levels and duration and control had no significant (P > 0.05) effect on days to emergence (DE), seedling wet weight (WW), dry weight (DW), chlorophyll, stem diameter, plant height and final root length (RL). Furthermore, seeds primed at lower concentration levels (0.05, 0.01 and 0.1%) with longer duration priming period (24 hours) for Mo, Zn and B recorded higher results on the seedling emergence and establishment parameters. The field investigation showed that priming with micronutrients solutions had no significant difference on the final values of dry biomass, prolificacy, harvest index and grain yield. Seeds primed with 0.05, 0.01 and 0.1 % concentration levels with longer duration priming period (24 hours) showed improvement in germination and seedling establishment. The grain yield and grain nutrient content was not improved, meanwhile emergence was improved. This confirms that not only micronutrients limit yields maximization and crop nutrients content retention solely, rather that the complexity of the agricultural crop production environment should be well understood by all farmers to archive their goals. Keywords: Boron, Maize, Micronutrients, Molybdenum, Nutrient seed priming, Zinc.
Thesis (M. Sc. Agriculture (Soil Science)) -- University of Limpopo, 2019
Keywords: Boron; Maize; Micronutrients; Molybdenum; Nutrient seed priming; Zinc; Corn; Micronutrient fertilizers; Zinc fertilizers